Antibiotics Drug Use Evaluation Among Patients With Kidney Disorder in PKU Muhammadiyah Hospital of Yogyakarta - Fentyana Dwi Rilawati; Agung Endro Nugroho; Inayati (Journal Pharmaceutical Science and Application, 2012)
Antibiotic that appropriately as used anti-infective has drug a great success in reducing morbidity and mortality rates resulted from various infectious diseases, leading its increasing usage. Antibiotic are generally eliminated through kidney. Patients with kidney disorder, dosage adjustment is recommended for certain antibiotics. This research aims at evaluating the use of antibiotics among patients with kidney disorder in the inpatient wards of PKU Muhammadiyah Hospital Yogyakarta. Data collection was done retrospectively based on medical record data of inpatients meeting both inclusion and exclusion criteria in PKU Muhammadiyah Hospital Yogyakarta. Data processing was done by using a descriptive analytical technique. Result of the study shows that there were 76 patients with kidney disorder using antibiotics and meet inclusion and exclusion criteria. In this study patients wasn’t shown an indications of infection is aproximately 75,00% (57 patients) and patient with indication infection were 25,00% (19 patients). From those who have an appropriate indication, it is just 21,05% (16 patient) have an appropriate medication, 23,68% (18 patient) is right patient and 22,37% (17 patient) have an appropriate doses. Clinical outcome of those 19 patient is good (14 patient) with inpatient duration less than 7 days for 12 patient. Total 76 patient with renal disorder who received antibiotics, 21,05% (16 patients) have inappropriate doses which is mean there is no doses adjusment according to the creatinine clearance of each patient. Keywords: Antibiotics; Kidney Disorders; Rational Drug; Dose